2022
DOI: 10.35877/454ri.daengku874
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Education, Income, Unemployment, and Poverty toward the Gini Ratio in Member of OIC Countries

Abstract: This study aims to observe the effect of the Gini Ratio with factors of education, income, unemployment, and poverty in OIC member countries. This study uses purposive sampling in collecting data in the form of 24 OIC countries between  2010-2019. The data were observed using a random effect model after the Chow and Iju Hausman tests were carried out. The results show that only poverty has a significant effect on the Gini ratio. Poverty which is certainly caused by inequality in income received against expendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
9
0
3
Order By: Relevance
“…In research conducted at the University of Bolton in the UK, it was found that students who are addicted to video games have a tendency or risk of suffering from Asperger's Syndrome. From this study also obtained results that video game addicts are at risk for mental health disorders such as depression (Fauziana et al, 2022). In this study, John Charlton and his colleagues studied 400 game addicts.…”
Section: Discussionmentioning
confidence: 77%
“…In research conducted at the University of Bolton in the UK, it was found that students who are addicted to video games have a tendency or risk of suffering from Asperger's Syndrome. From this study also obtained results that video game addicts are at risk for mental health disorders such as depression (Fauziana et al, 2022). In this study, John Charlton and his colleagues studied 400 game addicts.…”
Section: Discussionmentioning
confidence: 77%
“…Hasil pada tabel 2 bisa dilihat bahwa tidak adanya korelasi antara jumlah publikasi pada scopus dengan repositori karya ilmiah. Kurangnya topik yang relevan pada karya akhir yang berhubungan dengan studi yang akan diteliti oleh akademisi yang akan mengirimkan naskah mereka ke jurnal tujuan menjadi kendala utama tidak adanya korelasi antar kedua variabel tersebut (Fauziana et al, 2022). Pustakawan juga perlu berbenah untuk lebih berkontribusi pada kegiatan riset dan publikasi, sehingga koleksi karya akhir bisa dimanfaatkan dengan baik menjadi referensi untuk akademisi yang ingin menulis paper mereka kepada jurnal terindeks Scopus.…”
Section: Hasil Dan Pembahasanunclassified
“…Data dianalisis dengan metode Ordinal Least Square (OLS) untuk mengetahui pengaruh halaman terhadap jumlah sitasi. Studi ini menggunakan Eviews versi 10 full version untuk mengolah data (Fauziana et al, 2022).…”
Section: Metodeunclassified